Biochemical characterization, cloning and molecular modeling of a digestive lipase from red seabream (Pagrus major): Structural explanation of the interaction deficiency with colipase and lipidic interface. Issue 6 (6th February 2017) - Smichi, Nabil; Fendri, Ahmed; Triki, Soumaya; Arondel, Vincent; Rebai, Ahmed; Gargouri, Youssef; Miled, Nabil
Abstract : Red seabream digestive lipase (RsDL) was purified from fresh pyloric caeca. Pure RsDL has an apparent molecular mass of 50 kDa. The RsDL is more active on short‐chain triacylglycerols (TC4 ), and enzymatic activity decreases when medium (TC8 ) or long‐chain (olive oil) triacylglycerols were used as substrates. The specific activities of RsDL are very weak as compared to those obtained with classical pancreatic lipases. No colipase was detected in the red seabream pyloric caeca. Furthermore, the RsDL was not activated by a mammal colipase. Similar results were reported for annular seabream lipase. In order to explain structurally the discrepancies between sparidae and mammal lipases, genes encoding mature RsDL and five other lipases from sparidae fish species were cloned and sequenced. Phylogenetic studies indicated the closest homology of sparidae lipases to bird pancreatic ones. Structural models were built for annular seabream and RsDL under their closed and open forms using mammal pancreatic lipases as templates. Several differences were noticed when analyzing the amino acids corresponding to those involved in HPL binding to colipase. This is likely to prevent interaction between the fish lipase and the mammalian colipase and may explain the fact that mammalian colipase is not effective in activating sparidae lipases. In addition, several hydrophobic residues, playing a key role in anchoring pancreatic lipase onto the lipid interface, are replaced by polar residues in fish lipases. This might explain the reason why the latter enzymes display weak activity levels when compared to mammalian pancreatic lipases.